Pro-Inflammatory diet accounts for higher prevalence of retinopathy in diabetes participants rather than normal glucose and prediabetes: Results from NHANES, 2005–2008 - Pan, Wenjun; Zhang, Zhuqi; Zhang, Yuzhuo; Lu, Haining; Wang, Baohua; Zhao, Shaoyang; Li, Saimei (Frontiers in Nutrition, 2023)
Retinopathy is a chronic inflammatory disease whose prognosis could be improved with dietary intervene. However, the association between pro-inflammatory diet and the prevalence of retinopathy has not been fully elucidated. We conducted a cross-sectional study to assess the association between Dietary inflammatory index (DII) and the prevalence of retinopathy based on the data from National Health and Nutritional Examination Survey (NHANES) 2005–2008 involving 2,403 participants. Energy -adjusted DII (E-DII) was not related to the occurrence of retinopathy in the general, non-diabetic or middle-aged participants. In the diabetes and aged participants, one unit increment of E-DII accounted for 14% and 15% increase of the prevalence of retinopathy and the highest E-DII group had 78% and 79% higher prevalence of retinopathy than the lowest group respectively. After adjusted for several covariables, the highest E-DII group was still associated with 68% increase of retinopathy in diabetic patients. These results suggest that a pro-inflammatory diet is significantly associated with higher odds of diabetic retinopathy among diabetes patients.